1982
DOI: 10.1128/aem.43.3.509-513.1982
|View full text |Cite
|
Sign up to set email alerts
|

Ozone decontamination of bioclean rooms

Abstract: To establish a convenient method for decontaminating bioclean rooms, the effect of ozone at 80 mg/m3 for 72 h was compared with formaldehyde vaporization at an initial concentration of 150 mg/m3 with a gradual decrease to 20 mg/m3 during 72 h. Ozone was found to be inferior to formaldehyde in activity. When the bioclean room was decontaminated twice with ozone, the mean colony count per 10 cm2 was decreased to about the same level as when formaldehyde was used. Ozone had a strong caustic effect upon rubber mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The same results were reported in several previous studies [ 22 – 24 , 50 , 55 57 ]. This might be attributed to the maximum concentration of gaseous O 3 used in this study is lower than the minimal bactericidal that has been recommended in earlier studies [ 51 , 52 ]. Moreover, the times of exposure for gaseous O 3 used in the present study were short comparing to earlier studies, where there is consensus that increase the concentration of gaseous O 3 exposure time in hours will increase the rate of bacterial reduction [ 50 , 58 ].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The same results were reported in several previous studies [ 22 – 24 , 50 , 55 57 ]. This might be attributed to the maximum concentration of gaseous O 3 used in this study is lower than the minimal bactericidal that has been recommended in earlier studies [ 51 , 52 ]. Moreover, the times of exposure for gaseous O 3 used in the present study were short comparing to earlier studies, where there is consensus that increase the concentration of gaseous O 3 exposure time in hours will increase the rate of bacterial reduction [ 50 , 58 ].…”
Section: Discussionmentioning
confidence: 63%
“…This finding is consistent with the results of other studies investigating the effect of concentration of O 3 that is dissolved in water on the reduction in MBP [ 25 , 30 – 31 , 49 50 ]. The minimal bactericidal concentration of O 3 is still an area of debate, where Hamelin and Chung [ 29 ], demonstrated that the minimum bactericidal concentration of O3 is 1 ppm, whilst other studies have recommended values between 3 ppm and 4 ppm [ 25 ; 31 , 50 ] and 20 to 30 ppm for gaseous O3 [ 51 , 52 ]. On the other hand, we didn’t identify significant impact exposure time on RF especially at higher concentrations except rubber.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of O3 for disinfecting surfaces and rooms has been examined in several previous studies, and many of them have used low O3 concentrations because of the toxic nature of the gas and its relatively long half-life [58,[83][84][85][86]. Nevertheless, the use of low O3 concentrations generally leads to limited or inconclusive results.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ozone gas for the inactivation of vegetative and spore-forming microorganisms on surfaces has been explored since at least 1982 [4]. More recently, ozone gas has been tested and is gaining traction for use in healthcare environments [5] for disinfection (in particular, inactivation of vegetative bacteria [6] and viruses [7]) and sterilization (inactivation of sporeforming microorganisms such as B. anthracis, Clostridioides difficile [8], and Bacillus cereus [6]).…”
Section: Introductionmentioning
confidence: 99%